The Δ1-pyrroline-5-carboxylate synthetase family performs diverse physiological functions in stress responses in pear (Pyrus betulifolia) - Ma, Changqing; Wang, Mengqi; Zhao, Mingrui; Yu, Mengyuan; Zheng, Xiaodong; Tian, Yike; Sun, Zhijuan; Liu, Xiaoli; Wang, Caihong (Frontiers in Plant Science, 2022)
Δ1-Pyrroline-5-carboxylate synthetase (P5CS) acts as the rate-limiting enzyme in the biosynthesis of proline in plants. Although P5CS plays an essential role in plant responses to environmental stresses, its biological functions remain largely unclear in pear (Pyrus betulifolia). In the present study, 11 putative pear P5CSs (PbP5CSs) were identified by comprehensive bioinformatics analysis and classified into five subfamilies. Segmental and tandem duplications contributed to the expansion and evolution of the PbP5CS gene family. Various cis-acting elements associated with plant development, hormone responses, and/or stress responses were identified in the promoters of PbP5CS genes. To investigate the regulatory roles of PbP5CS genes in response to abiotic and biotic stresses, gene expression patterns in publicly available data were explored. The tissue-specific expressional dynamics of PbP5CS genes indicate potentially important roles in pear growth and development. Their spatiotemporal expression patterns suggest key functions in multiple environmental stress responses. Transcriptome and real-time quantitative PCR analyses revealed that most PbP5CS genes exhibited distinct expression patterns in response to drought, waterlogging, salinity-alkalinity, heat, cold, and infection by Alternaria alternate and Gymnosporangium haraeanum. The results provide insight into the versatile functions of the PbP5CS gene family in stress responses. The findings may assist further exploration of the physiological functions of PbP5CS genes for the development and enhancement of stress tolerance in pear and other fruits.